Method for preparing zirconia toughened alumina ceramic wedge
Patent Information
- Application Number
- CN202610780487.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-06-02
AI Technical Summary
低固含量带来一系列工艺难题:脱脂和烧结过程中,坯体收缩率极大(常超过20%),且收缩各向异性显著,易发生弯曲、扭曲等变形;同时,较大的线性收缩使生坯尺寸精度难以控制,烧结后毛坯必须经过大量精密磨削加工才能达到亚微米级公差与表面质量,不仅加工成本高、周期长,也导致材料利用率低
(1)本发明氧化锆增韧氧化铝陶瓷劈刀的制备方法采用“喷雾滴定共沉淀-低温煅烧”的粉体工艺路线制备了强度适中、尺寸可控的“团聚”粉体。该“团聚”粉体具有足够的机械强度,能够在喂料混炼与注射过程中保持结构不被破坏,从而大幅提高注射喂料的陶瓷固含量(体积分数可提升至55%以上)。同时,由于原粉为化学共沉淀法结合喷雾滴定制备,其化学成分均匀,一次晶粒尺寸细小(可达纳米级),烧结活性高,保证了最终烧结体可获得细小、均匀的晶粒组织,从而实现优异的机械性能。
Smart Images

Figure CN122344109B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic material preparation technology, specifically relating to a method for preparing a zirconia-toughened alumina ceramic chopping tool. Background Technology
[0002] Ceramic cleavers are key tools in semiconductor packaging and microelectronic interconnection, primarily used in wire bonding processes. Their function is to precisely guide and clamp metal wires such as gold, copper, and aluminum, establishing reliable electrical and mechanical connections between chip electrodes and external pins. As integrated circuits continue to evolve towards higher density, smaller size, and higher performance, increasingly stringent requirements are placed on the dimensional accuracy, wear resistance, high-temperature stability, and lifespan of cleavers. Against this backdrop, zirconia-toughened alumina (ZTA) ceramic materials exhibit significant advantages. This material uses alumina as a matrix and introduces a zirconia phase transformation toughening mechanism. While maintaining the inherent high hardness, high wear resistance, and good insulation of alumina, it significantly improves fracture toughness and thermal shock resistance, thus becoming the preferred material for manufacturing high-performance, long-life cleavers. This is crucial for ensuring bonding process stability, improving packaging yield, and reducing tooling costs.
[0003] Currently, ZTA ceramic chopping tools are mainly manufactured using injection molding. This technology is suitable for the mass production of complex axisymmetric parts, and can efficiently form the slender through holes and precise head contours required for chopping tools. However, to obtain excellent mechanical properties (such as high strength and high wear resistance), the sintered body is usually required to have a uniform and fine grain structure, which relies on ultrafine or nanoscale ZTA powder as raw material. Ultrafine powder has a large specific surface area and high surface energy. When preparing injection feedstock, a large amount of organic binder is needed to coat the powder surface to ensure flowability and uniformity, resulting in a generally low ceramic solid content in the feedstock (usually less than 50% by volume). The low solid content brings a series of process challenges: during debinding and sintering, the shrinkage rate of the green body is extremely high (often exceeding 20%), and the shrinkage anisotropy is significant, making it prone to bending, twisting, and other deformations; at the same time, the large linear shrinkage makes it difficult to control the dimensional accuracy of the green body. After sintering, the green body must undergo a large amount of precision grinding to achieve submicron tolerances and surface quality, which not only results in high processing costs and long cycles, but also leads to low material utilization. More significantly, deformation and processing losses lead to a decrease in yield, which significantly increases the manufacturing cost of high-performance ZTA ceramic chopping tools and restricts their further promotion and application.
[0004] Therefore, the challenge lies in how to effectively increase the solid content of the injection feedstock while ensuring that ZTA ceramic cleavers achieve fine grains, high density, and excellent mechanical properties, thereby reducing sintering shrinkage and deformation, minimizing subsequent processing, and ultimately achieving a balance between high yield and low cost. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing a zirconia toughened alumina ceramic chopping tool that combines high toughness, high wear resistance, high dimensional accuracy, high yield and low cost, in order to overcome the shortcomings of the prior art.
[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is as follows: A method for preparing a zirconia-toughened alumina ceramic cleaver includes the following steps: (1) Dissolve aluminum salt, zirconium salt and yttrium salt together in water to prepare a mixed solution of metal ions; (2) Mix the precipitant, dispersant and water to obtain a precipitant solution; (3) The mixed metal ion solution is spray-titrated into the precipitant solution while the reaction solution is stirred during titration; (4) After titration, a polar organic solvent is added to the reaction solution, stirring is continued, and the pH is adjusted to alkaline with ammonia water for aging; the polar organic solvent is miscible with water, has a surface tension lower than that of water, and a dielectric constant lower than that of water. (5) Separate the solid and liquid components of the aged product, wash it with water, and prepare a suspension as a precursor slurry; (6) The precursor slurry is granulated and calcined at 900℃~1100℃ to obtain ceramic powder; (7) The ceramic powder is mixed with a low molecular weight polymer, stearic acid, a medium molecular weight polymer and a high molecular weight polymer to obtain an injection feed; the molecular weight of the low molecular weight polymer, the medium molecular weight polymer and the high molecular weight polymer increases sequentially, and the peak thermal decomposition temperature increases sequentially; the low molecular weight polymer is a flow agent; the medium molecular weight polymer and the high molecular weight polymer are both binders; (8) Cool and crush the injection feed to obtain injection feed particles; (9) The injection-feed particles are injection molded to obtain a ceramic chopping green body; (10) The ceramic green body is pre-sintered to obtain a ceramic body. The pre-sintering is a gradient heating sintering, including the first stage of heating to 500℃~700℃ and holding for 0.5 h~2 h, the second stage of heating to 1100℃~1300℃ and holding for 2 h~5 h, and the third stage of heating to 1350℃~1500℃ and holding for 2 h~5 h. (11) The ceramic blank is subjected to hot isostatic pressing sintering, grinding, processing and polishing to obtain a ceramic chopping knife.
[0007] In the above-mentioned method for preparing zirconia toughened alumina ceramic chopping knife, preferably, in step (4), the amount of the polar organic solvent used is 10% to 30% of the sum of the water mass in steps (1) and (2).
[0008] In the preferred embodiment of the above-mentioned method for preparing zirconia-toughened alumina ceramic chopping knife, in step (1), the mass fraction ratio of the aluminum salt, zirconium salt, yttrium salt, and water is 5%–10% : 0.5%–1% : 0.01%–0.1% : 89%–94%; In step (2), the mass fraction ratio of the precipitant, dispersant and water is 4%–14% : 0.01%–1% : 85%–95%; In step (7), the mass fraction ratio of the ceramic powder to the low molecular weight polymer, stearic acid, medium molecular weight polymer and high molecular weight polymer is 75%~85%∶2%~10%∶0.5%~3%∶2%~10%∶4%~20%.
[0009] In the above-mentioned method for preparing zirconia-toughened alumina ceramic cleaver, preferably, in step (1), the aluminum salt is ammonium aluminum sulfate, the zircon salt is zirconium oxychloride, and the yttrium salt is yttrium nitrate; In step (2), the precipitant is selected from at least one of ammonium bicarbonate and ammonium carbonate; the dispersant is selected from at least one of polyethylene glycol and polyvinylpyrrolidone. In step (4), the polar organic solvent is at least one of anhydrous ethanol, methanol, acetone and isopropanol; In step (7), the low molecular weight polymer is at least one of paraffin wax and beeswax; the medium molecular weight polymer is at least one of acrylic resin and polyethylene wax; and the high molecular weight polymer is at least one of polystyrene, ethylene-vinyl acetate copolymer, polyethylene, polypropylene and polyvinyl butyral.
[0010] In the above-mentioned method for preparing zirconia-toughened alumina ceramic chopping knife, preferably, in step (3), the spraying and dripping speed is 20 ml / min to 250 ml / min, and the stirring speed is 50 r / min to 150 r / min; In step (4), the pH of the reaction solution after adjustment with ammonia is 7.6 to 9.0, and the aging time is 1 h to 24 h; In step (6), the granulation is carried out by spray granulation, the temperature of the spray granulation is 150℃~300℃; the calcination time is 1h~5h; In step (7), the mixing is carried out using an internal mixer, and the temperature of the internal mixer is set to 140℃~170℃.
[0011] In the preferred method for preparing the zirconia-toughened alumina ceramic chopping tool, in step (9), the injection temperature is 160℃~190℃, the injection pressure is 5MPa~15MPa, the molding holding pressure is 5MPa~10MPa, and the molding holding time is 20s~60s.
[0012] In the preferred method for preparing the zirconia-toughened alumina ceramic cleaver described above, in step (10), the heating rate of the first stage is 0.2℃ / min to 0.5℃ / min, the heating rate of the second stage is 2℃ / min to 5℃ / min, and the heating rate of the third stage is 2℃ / min to 5℃ / min.
[0013] In the above-mentioned method for preparing zirconia toughened alumina ceramic chopping knife, preferably, in step (11), the hot isostatic pressing sintering temperature is 1400℃~1500℃ and the holding time is 1h~3h.
[0014] In the preferred method for preparing the zirconia-toughened alumina ceramic chopping knife, step (5) involves filtering the precipitate to obtain a solid product, adding water at a mass of 2 to 5 times that of the solid product, stirring, and filtering; the number of water washes is 2 to 5 times.
[0015] In the above-mentioned method for preparing zirconia-toughened alumina ceramic chopping tools, preferably, in step (8), the size of the injection feed particles is 2mm to 5mm.
[0016] Compared with the prior art, the advantages of the present invention are as follows: (1) The preparation method of the zirconia toughened alumina ceramic chopping tool of the present invention adopts the powder process route of "spray titration co-precipitation-low temperature calcination" to prepare "agglomerated" powder with moderate strength and controllable size. The "agglomerated" powder has sufficient mechanical strength and can maintain its structure without being destroyed during feeding, mixing and injection, thereby significantly increasing the ceramic solid content of the injection feed (volume fraction can be increased to more than 55%). At the same time, since the original powder is prepared by chemical co-precipitation combined with spray titration, its chemical composition is uniform, the primary grain size is small (up to nanometer level), and the sintering activity is high, ensuring that the final sintered body can obtain a fine and uniform grain structure, thereby achieving excellent mechanical properties.
[0017] (2) In traditional coprecipitation processes, aqueous solvents are typically used as the reaction solvent. The synthesized precursors are prone to agglomeration, resulting in powders with low dispersibility after calcination, which is detrimental to sintering. Alternatively, a large amount of ethanol is added as a cosolvent at the initial stage of the reaction to reduce the dielectric constant, promote nucleation, and inhibit agglomeration by utilizing its steric hindrance. However, when using a mixed alcohol-water solvent as the initial reaction solvent, the solubility of metal ions or precipitants in the mixed solvent is low, reducing the reactant concentration and affecting the coprecipitation reaction efficiency and precursor yield. In this invention, the coprecipitation reaction is first carried out in an aqueous medium. When the titration is complete but the reaction is not yet finished, a polar organic solvent, such as anhydrous ethanol, is immediately added to the system. This significantly reduces the dielectric constant of the solvent, thereby reducing the solubility product of the precipitate. At this time, since the reaction is still ongoing, it can promote the increase in the number of precursor nuclei in the reaction system and regulate the nucleus growth rate; at the same time, it can ensure the same reaction efficiency and precursor yield as with aqueous solvents. Furthermore, the low polarity and steric hindrance of polar organic solvents can also be used to reduce the agglomeration of reaction products, thereby achieving controllable dispersion / agglomeration of nanoparticles. This method allows polar organic solvents to act directly on the key stages of nucleation and growth, improving reaction and precipitation efficiency, thus optimizing the process and improving cost-effectiveness while ensuring product performance.
[0018] (3) In the preparation method of the zirconia-toughened alumina ceramic chopping tool of the present invention, the ceramic blank is pre-sintered through staged heat preservation, especially in the relatively low temperature range of 1100℃ to 1300℃, which can promote the full and uniform solid solution reaction between yttrium oxide and zirconia, and effectively inhibit the reaction between yttrium oxide and alumina to form unfavorable impurity phases such as yttrium aluminum garnet. After completing the atmospheric pressure sintering, the ceramic blank is further subjected to hot isostatic pressing treatment, which can effectively eliminate the residual micro closed pores in the sintered body, promote grain boundary migration and material diffusion, and make the material reach a fully densified state close to the theoretical density. This further improves the hardness, elastic modulus, wear resistance and reliability of the material, reduces performance dispersion, and makes the chopping tool exhibit a higher service life and stability in long-term, high-frequency wire bonding operations.
[0019] (4) The preparation method of the present invention uses polymers of different molecular weights when preparing injection feed, namely low molecular weight polymers, medium molecular weight polymers and high molecular weight polymers with different thermal decomposition temperatures during the thermal degreasing process, so as to form continuous pore channels during the degreasing process, realize gradient degreasing, thereby avoiding cracks or deformation of the green body, and improving degreasing efficiency and green body strength.
[0020] (5) Traditional spray coprecipitation uses an upper-suspended stirrer for stirring. During rapid titration, the stirring rod will have an adverse effect on the uniformity of the spray titration distribution on the entire liquid surface. This invention improves the stirring method by changing the upper-suspended stirrer to a bottom-mounted stirrer to strongly stir the reaction solution.
[0021] In summary, this invention solves the problems of low solid content, large deformation, difficult processing, and high cost in the injection molding of high-performance ZTA ceramic cleavers. While ensuring that the product has mechanical properties such as fine grains, high toughness, and high wear resistance, it achieves a balance between high dimensional accuracy, high yield, and low manufacturing cost. Attached Figure Description
[0022] Figure 1 The image shows the morphology of ZTA powder prepared by the preparation method of Example 1 of this invention.
[0023] Figure 2 Microstructure of the cross-section of the ZTA ceramic chopping tool prepared by the preparation method of Example 1 of the present invention.
[0024] Figure 3 Morphology of ZTA powder prepared by the method of Comparative Example 1.
[0025] Figure 4 Morphology of ZTA powder prepared by the method of Comparative Example 2. Detailed Implementation
[0026] The present invention will be further described below with reference to the specification and specific preferred embodiments, but this does not limit the scope of protection of the present invention. Unless otherwise specified, the materials and instruments used in the following embodiments are commercially available.
[0027] Example 1 The present invention discloses a method for preparing a zirconia-toughened alumina ceramic chopping tool, comprising the following steps: (1) Weigh 725.3g AlNH4(SO4)2·12H2O, 62.4g ZrOCl2·8H2O, 4.6g Y(NO3)3·6H2O and 10kg deionized water and put them into a beaker and stir to dissolve them to obtain a mixed solution of metal ions.
[0028] (2) Weigh 650g NH4HCO3, 2.5g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0029] (3) Use a peristaltic pump to transfer the metal ion mixed solution and titrate it into the reaction vessel by spray titration. Install a stirrer at the bottom of the reaction vessel to vigorously stir the reaction solution while titrating. The spray titration speed is 150 ml / min and the stirring speed is 100 r / min.
[0030] (4) After titration, add 2000g of anhydrous ethanol to the solution and continue stirring for 20 min. Adjust the pH of the solution to 8 with ammonia water and then age it.
[0031] (5) After aging, discard the supernatant and pour the precipitate into a positive pressure filter for solid-liquid separation. After separation, add deionized water to the solid product for washing, stir for 30 minutes, and then pour it into the filter for solid-liquid separation again. The mass of deionized water is twice the mass of the solid product, and the washing is performed 3 times. After washing, add an equal mass of deionized water to the solid product and stir to form a suspension to obtain the precursor slurry.
[0032] (6) The precursor slurry was transferred using a peristaltic pump and dried and granulated using spray granulation to obtain precursor particles. The spray granulation temperature was 220 °C. The precursor particles were then placed in a muffle furnace for sintering to obtain ceramic powder (hereinafter referred to as ZTA powder). The sintering temperature was 1100 °C and the holding time was 2 h. Steps (1) to (6) were repeated 10 times to prepare sufficient ZTA powder for subsequent use.
[0033] (7) Weigh 850g ZTA powder, 45g paraffin, 7.5g stearic acid, 30g acrylic resin, 37.5g polystyrene and 30g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0034] (8) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0035] (9) Place the injection feed particles in the hopper and use an injection molding machine to perform injection molding to obtain a ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 9 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 30 s.
[0036] (10) The ceramic cleaver blank is placed in a muffle furnace for pre-sintering. The sintering regime is to raise the temperature to 600℃ at 0.3℃ / min and hold for 0.5h, then raise the temperature to 1250℃ at 4℃ / min and hold for 3h, and finally raise the temperature to 1450℃ at 2℃ / min and hold for 3h.
[0037] (11) The pre-sintered ceramic blank is placed in an AIP10-30H high-temperature hot isostatic pressing furnace for hot isostatic pressing sintering at a temperature of 1450℃ and a holding time of 1h. The sintered cleaver is then ground, processed and polished to obtain a zirconia toughened alumina ceramic cleaver, namely ZTA ceramic cleaver.
[0038] Example 2 The present invention discloses a method for preparing a zirconia-toughened alumina ceramic chopping tool, comprising the following steps: (1) Weigh 870.4g AlNH4(SO4)2·12H2O, 74.9g ZrOCl2·8H2O, 5.5g Y(NO3)3·6H2O and 10kg deionized water and place them in a beaker and stir to dissolve to obtain a mixed solution of metal ions.
[0039] (2) Weigh 780g NH4HCO3, 3g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0040] (3) Use a peristaltic pump to transfer the metal ion mixed solution and titrate it into the reaction vessel by spray titration. While titrating, vigorously stir the reaction solution. The spray titration speed is 150 ml / min and the stirring speed is 100 r / min.
[0041] (4) After titration, add 2000g of anhydrous ethanol to the solution and continue stirring for 20 min. Adjust the pH of the solution to 8 with ammonia water and then age it.
[0042] (5) After aging, discard the supernatant and pour the precipitate into a positive pressure filter for solid-liquid separation. After separation, add deionized water to the solid product for washing, stir for 30 minutes, and then pour it into the filter for solid-liquid separation again. The mass of deionized water is twice the mass of the solid product, and the washing is performed 3 times. After washing, add an equal mass of deionized water to the solid product and stir to form a suspension to obtain the precursor slurry.
[0043] (6) The slurry was transferred using a peristaltic pump, and the precursor slurry was dried and granulated using spray granulation to obtain precursor particles. The spray granulation temperature was 220 °C. The precursor particles were then placed in a muffle furnace for sintering to obtain ZTA powder. The sintering temperature was 1000 °C, and the holding time was 3 h. Steps (1) to (6) were repeated 10 times to prepare sufficient ZTA powder for subsequent use.
[0044] (7) Weigh 850g ZTA powder, 45g paraffin wax, 7.5g stearic acid, 30g acrylic resin, 37.5g polystyrene and 30g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0045] (8) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0046] (9) Place the injection feed particles in the hopper and use an injection molding machine to perform injection molding to obtain a ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 9 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 30 s.
[0047] (10) The ceramic cleaver blanks were placed in a muffle furnace for pre-sintering. The sintering regime was to raise the temperature to 600℃ at 0.3℃ / min and hold for 0.5h, then raise the temperature to 1300℃ at 4℃ / min and hold for 3h, and finally raise the temperature to 1500℃ at 2℃ / min and hold for 2h.
[0048] (11) The pre-sintered ceramic blank is subjected to hot isostatic pressing sintering at a temperature of 1450℃ and a holding time of 1h; the sintered chopping knife is then ground, processed and polished to obtain ZTA ceramic chopping knife.
[0049] Example 3 The present invention discloses a method for preparing a zirconia-toughened alumina ceramic chopping tool, comprising the following steps: (1) Weigh 725.3g AlNH4(SO4)2·12H2O, 62.4g ZrOCl2·8H2O, 4.6g Y(NO3)3·6H2O and 10kg deionized water and put them into a beaker and stir to dissolve them to obtain a mixed solution of metal ions.
[0050] (2) Weigh 650g NH4HCO3, 2.5g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0051] (3) Use a peristaltic pump to transfer the metal ion mixed solution and titrate it into the reaction vessel by spray titration. While titrating, vigorously stir the reaction solution. The spray titration speed is 100 ml / min and the stirring speed is 100 r / min.
[0052] (4) After titration, add 4000g of anhydrous ethanol to the solution and continue stirring for 20 min. Adjust the pH of the solution to 8 with ammonia water and then age it.
[0053] (5) After aging, discard the supernatant and pour the precipitate into a positive pressure filter for solid-liquid separation. After separation, add deionized water to the solid product for washing, stir for 30 minutes, and then pour it into the filter for solid-liquid separation again. The mass of deionized water is twice the mass of the solid product, and the washing is performed 3 times. After washing, add an equal mass of deionized water to the solid product and stir to form a suspension to obtain the precursor slurry.
[0054] (6) The slurry was transferred using a peristaltic pump, and the precursor slurry was dried and granulated using spray granulation to obtain precursor particles. The spray granulation temperature was 220 °C. The precursor particles were then placed in a muffle furnace for sintering to obtain ZTA powder. The sintering temperature was 1000 °C, and the holding time was 3 h. Steps (1) to (6) were repeated 10 times to prepare sufficient ZTA powder for subsequent use.
[0055] (7) Weigh 840g ZTA powder, 48g paraffin wax, 8.0g stearic acid, 32g acrylic resin, 40g polystyrene and 32g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0056] (8) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0057] (9) Place the injection feed particles in the hopper and use an injection molding machine to perform injection molding to obtain a ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 10 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 40 s.
[0058] (10) The ceramic cleaver blanks were placed in a muffle furnace for pre-sintering. The sintering regime was to raise the temperature to 600℃ at 0.3℃ / min and hold for 0.5h, then raise the temperature to 1300℃ at 4℃ / min and hold for 2h, and finally raise the temperature to 1450℃ at 2℃ / min and hold for 3h.
[0059] (11) The pre-sintered ceramic blank is subjected to hot isostatic pressing sintering at a temperature of 1475℃ and a holding time of 1h; the sintered chopping knife is then ground, processed and polished to obtain ZTA ceramic chopping knife.
[0060] Example 4 The present invention discloses a method for preparing a zirconia-toughened alumina ceramic chopping tool, comprising the following steps: (1) Weigh 659.4g AlNH4(SO4)2·12H2O, 56.7g ZrOCl2·8H2O, 4.2g Y(NO3)3·6H2O and 10kg deionized water and place them in a beaker and stir to dissolve them to obtain a mixed solution of metal ions.
[0061] (2) Weigh 650g NH4HCO3, 2.3g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0062] (3) Use a peristaltic pump to transfer the metal ion mixed solution and titrate it into the reaction vessel by spray titration. While titrating, vigorously stir the reaction solution. The spray titration speed is 150 ml / min and the stirring speed is 100 r / min.
[0063] (4) After titration, add 2000g of anhydrous ethanol to the solution and continue stirring for 20 min. Adjust the pH of the solution to 8 with ammonia water and then age it.
[0064] (5) After aging, discard the supernatant and pour the precipitate into a positive pressure filter for solid-liquid separation. After separation, add deionized water to the solid product for washing, stir for 30 minutes, and then pour it into the filter for solid-liquid separation again. The mass of deionized water is twice the mass of the solid product, and the washing is performed 3 times. After washing, add an equal mass of deionized water to the solid product and stir to form a suspension to obtain the precursor slurry.
[0065] (6) The precursor slurry was transferred using a peristaltic pump and dried and granulated using spray granulation to obtain precursor particles. The spray granulation temperature was 220 °C. The precursor particles were then sintered in a muffle furnace to obtain ZTA powder. The sintering temperature was 1100 °C and the holding time was 2 h. Steps (1) to (6) were repeated 10 times to prepare sufficient ZTA powder for subsequent use.
[0066] (7) Weigh 840g ZTA powder, 48g paraffin wax, 8.0g stearic acid, 32g acrylic resin, 40g polystyrene and 32g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0067] (8) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0068] (9) Place the injection feed particles in the hopper and use an injection molding machine to perform injection molding to obtain a ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 10 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 30 s.
[0069] (10) The ceramic cleaver blank is placed in a muffle furnace for pre-sintering. The sintering regime is to raise the temperature to 600℃ at 0.3℃ / min and hold it for half an hour, then raise the temperature to 1300℃ at 4℃ / min and hold it for 2 hours, and finally raise the temperature to 1500℃ at 2℃ / min and hold it for 2 hours.
[0070] (11) The pre-sintered ceramic blank is subjected to hot isostatic pressing sintering at a temperature of 1450℃ and a holding time of 1h; the sintered chopping knife is then ground, processed and polished to obtain ZTA ceramic chopping knife.
[0071] Comparative Example 1 A method for preparing a zirconia-toughened alumina ceramic chopping tool is basically the same as that in Example 1, except that anhydrous ethanol is not added in step (4). The specific steps are as follows: (1) Weigh 725.3g AlNH4(SO4)2·12H2O, 62.4g ZrOCl2·8H2O, 4.6g Y(NO3)3·6H2O and 10kg deionized water and put them into a beaker and stir to dissolve them to obtain a mixed solution of metal ions.
[0072] (2) Weigh 650g NH4HCO3, 2.5g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0073] (3) The metal ion mixed solution is transferred using a peristaltic pump and titrated into the reaction vessel by spray titration. The reaction solution is vigorously stirred while titrating. The spray titration speed range is 150 ml / min and the stirring rate is 100 r / min.
[0074] (4) After titration, continue stirring for 20 min and adjust the pH of the solution to 8 with ammonia water, and then age it.
[0075] (5) After aging, the supernatant is discarded and the precipitated product is poured into a positive pressure filter for solid-liquid separation. After separation, deionized water is added to the solid product for washing. After stirring for 30 minutes, it is poured into the filter for solid-liquid separation. The mass of deionized water is twice the mass of the solid product, and the number of water washings is 3.
[0076] (6) Add an equal mass of deionized water to the solid product obtained after water washing and stir to form a suspension to obtain the precursor slurry.
[0077] (7) Use a peristaltic pump to transfer the slurry, and use spray granulation to dry and granulate the precursor slurry to obtain precursor particles. The spray granulation temperature is 220 °C.
[0078] (8) The precursor particles were placed in a muffle furnace for sintering to obtain ZTA powder. The sintering temperature was 1100℃ and the holding time was 2 h.
[0079] (9) After repeating steps (1-8) 10 times, weigh 850g ZTA powder, 45g paraffin wax, 7.5g stearic acid, 30g acrylic resin, 37.5g polystyrene, and 30g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0080] (10) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0081] (11) Place the feed pellets in the hopper and use an injection molding machine to inject them to obtain ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 9 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 30 s.
[0082] (12) The ceramic cleaver blanks were placed in a muffle furnace for pre-sintering. The sintering regime was to raise the temperature to 600℃ at 0.3℃ / min and hold for half an hour, then raise the temperature to 1250℃ at 4℃ / min and hold for 3 hours, and finally raise the temperature to 1450℃ at 2℃ / min and hold for 3 hours.
[0083] (13) The pre-sintered ceramic blank is placed in hot isostatic pressing for sintering at a temperature of 1450℃ and a holding time of 1h.
[0084] (14) The ZTA ceramic chopping knife is obtained by grinding, processing and polishing the sintered chopping knife.
[0085] Comparative Example 2 A method for preparing a zirconia-toughened alumina ceramic chopping tool is basically the same as that in Example 1, except that the anhydrous ethanol in step (4) is added in step (1) earlier. Due to the change in the order of adding polar solvents, the ZTA powder obtained is finer and the specific surface area is increased. The original formula in step (7) is insufficient to produce injectable feedstock, and more binder is required, so adjustments are made. The specific steps are as follows: (1) Weigh 725.3g AlNH4(SO4)2·12H2O, 62.4g ZrOCl2·8H2O, 4.6g Y(NO3)3·6H2O, 10kg deionized water and 2000g anhydrous ethanol into a beaker and stir to dissolve to obtain a mixed solution of metal ions.
[0086] (2) Weigh 650g NH4HCO3, 2.5g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0087] (3) Use a peristaltic pump to transfer the metal ion mixed solution and titrate it into the reaction vessel by spray titration. While titrating, vigorously stir the reaction solution. The spray titration speed is 150 ml / min and the stirring speed is 100 r / min.
[0088] (4) After titration, continue stirring for 20 min and adjust the pH of the solution to 8 with ammonia water, and then age it.
[0089] (5) After aging, discard the supernatant and pour the precipitate into a positive pressure filter for solid-liquid separation. After separation, add deionized water to the solid product for washing, stir for 30 minutes, and then pour it into the filter for solid-liquid separation again. The mass of deionized water is twice the mass of the solid product, and the washing is performed 3 times. After washing, add an equal mass of deionized water to the solid product and stir to form a suspension to obtain the precursor slurry.
[0090] (6) The precursor slurry was transferred using a peristaltic pump and dried and granulated using spray granulation to obtain precursor particles. The spray granulation temperature was 220 °C. The precursor particles were then sintered in a muffle furnace to obtain ZTA powder. The sintering temperature was 1100 °C and the holding time was 2 h. Steps (1) to (6) were repeated 10 times to prepare sufficient ZTA powder for subsequent use.
[0091] (7) Weigh 810g ZTA powder, 57g paraffin wax, 9.5g stearic acid, 38g acrylic resin, 47.5g polystyrene and 38g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0092] (8) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0093] (9) Place the injection feed particles in the hopper and use an injection molding machine to perform injection molding to obtain a ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 9 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 30 s.
[0094] (10) The ceramic cleaver blank is placed in a muffle furnace for pre-sintering. The sintering regime is to raise the temperature to 600℃ at 0.3℃ / min and hold for 0.5h, then raise the temperature to 1250℃ at 4℃ / min and hold for 3h, and finally raise the temperature to 1450℃ at 2℃ / min and hold for 3h.
[0095] (11) The pre-sintered ceramic blank is subjected to hot isostatic pressing sintering at a temperature of 1450℃ and a holding time of 1h; the sintered chopping knife is then ground, processed and polished to obtain ZTA ceramic chopping knife.
[0096] Comparative Example 3 A method for preparing a zirconia-toughened alumina ceramic cleaver is basically the same as that in Example 1, except that the sintering temperature in step (6) is reduced to 800℃. Since the ZTA powder obtained by sintering at 800℃ has a lower degree of "agglomeration", it will be sheared and dispersed during the mixing process in step (7). In addition, the sintering temperature is low, the grain development is incomplete, the original crystal size is smaller, and more binder is needed. Therefore, the solid content is reduced, and the formula in step (7) needs to be adjusted to obtain the injection feed. The specific steps are as follows: (1) Weigh 725.3g AlNH4(SO4)2·12H2O, 62.4g ZrOCl2·8H2O, 4.6g Y(NO3)3·6H2O and 10kg deionized water and put them into a beaker and stir to dissolve them to obtain a mixed solution of metal ions.
[0097] (2) Weigh 650g NH4HCO3, 2.5g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0098] (3) Use a peristaltic pump to transfer the metal ion mixed solution and titrate it into the reaction vessel by spray titration. While titrating, vigorously stir the reaction solution. The spray titration speed is 150 ml / min and the stirring speed is 100 r / min.
[0099] (4) After titration, add 2000g of anhydrous ethanol to the solution and continue stirring for 20 min. Adjust the pH of the solution to 8 with ammonia water and then age it.
[0100] (5) After aging, discard the supernatant and pour the precipitate into a positive pressure filter for solid-liquid separation. After separation, add deionized water to the solid product for washing, stir for 30 minutes, and then pour it into the filter for solid-liquid separation again. The mass of deionized water is twice the mass of the solid product, and the washing is performed 3 times. After washing, add an equal mass of deionized water to the solid product and stir to form a suspension to obtain the precursor slurry.
[0101] (6) The precursor slurry was transferred using a peristaltic pump and dried and granulated using spray granulation to obtain precursor particles at a temperature of 220 °C. The precursor particles were then sintered in a muffle furnace to obtain ZTA powder at a temperature of 800 °C for 2 h. Steps (1) to (6) were repeated 10 times to prepare sufficient ZTA powder for subsequent use.
[0102] (7) Weigh 800g ZTA powder, 60g paraffin wax, 10g stearic acid, 40g acrylic resin, 50g polystyrene and 40g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0103] (8) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0104] (9) Place the injection feed particles in the hopper and use an injection molding machine to perform injection molding to obtain a ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 9 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 30 s.
[0105] (10) The ceramic cleaver blank is placed in a muffle furnace for pre-sintering. The sintering regime is to raise the temperature to 600℃ at 0.3℃ / min and hold for 0.5h, then raise the temperature to 1250℃ at 4℃ / min and hold for 3h, and finally raise the temperature to 1450℃ at 2℃ / min and hold for 3h.
[0106] (11) The pre-sintered ceramic blank is subjected to hot isostatic pressing sintering at a temperature of 1450℃ and a holding time of 1h; the sintered chopping knife is then ground, processed and polished to obtain ZTA ceramic chopping knife.
[0107] Comparative Example 4 A method for preparing a zirconia-toughened alumina ceramic chopping knife is basically the same as that in Example 1, except that the calcination temperature in step (6) is 1250℃. The specific steps are as follows: (1) Weigh 725.3g AlNH4(SO4)2·12H2O, 62.4g ZrOCl2·8H2O, 4.6g Y(NO3)3·6H2O and 10kg deionized water and put them into a beaker and stir to dissolve them to obtain a mixed solution of metal ions.
[0108] (2) Weigh 650g NH4HCO3, 2.5g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0109] (3) Use a peristaltic pump to transfer the metal ion mixed solution and titrate it into the reaction vessel by spray titration. While titrating, vigorously stir the reaction solution. The spray titration speed is 150 ml / min and the stirring speed is 100 r / min.
[0110] (4) After titration, add 2000g of anhydrous ethanol to the solution and continue stirring for 20 min. Adjust the pH of the solution to 8 with ammonia water and then age it.
[0111] (5) After aging, discard the supernatant and pour the precipitate into a positive pressure filter for solid-liquid separation. After separation, add deionized water to the solid product for washing, stir for 30 minutes, and then pour it into the filter for solid-liquid separation again. The mass of deionized water is twice the mass of the solid product, and the washing is performed 3 times. After washing, add an equal mass of deionized water to the solid product and stir to form a suspension to obtain the precursor slurry.
[0112] (6) The precursor slurry was transferred using a peristaltic pump and dried and granulated using spray granulation to obtain precursor particles at a temperature of 220 °C. The precursor particles were then sintered in a muffle furnace to obtain ZTA powder at a temperature of 1250 °C for 2 h. Steps (1) to (6) were repeated 10 times to prepare sufficient ZTA powder for subsequent use.
[0113] (7) Weigh 850g ZTA powder, 45g paraffin wax, 7.5g stearic acid, 30g acrylic resin, 37.5g polystyrene and 30g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0114] (8) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0115] (9) Place the injection feed particles in the hopper and use an injection molding machine to perform injection molding to obtain a ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 9 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 30 s.
[0116] (10) The ceramic cleaver blanks were placed in a muffle furnace for pre-sintering. The sintering regime was to raise the temperature to 600℃ at 0.3℃ / min and hold for 0.5h, then raise the temperature to 1250℃ at 4℃ / min and hold for 3h, and finally raise the temperature to 1450℃ at 2℃ / min and hold for 3h.
[0117] (11) The pre-sintered ceramic blank is subjected to hot isostatic pressing sintering at a temperature of 1450℃ and a holding time of 1h; the sintered chopping knife is then ground, processed and polished to obtain ZTA ceramic chopping knife.
[0118] Comparative Example 5 A method for preparing a zirconia-toughened alumina ceramic chopping knife is basically the same as that in Example 1, except that the pre-sintering temperature in step (10) is raised to 1250℃ without heat preservation. The specific steps are as follows: (1) Weigh 725.3g AlNH4(SO4)2·12H2O, 62.4g ZrOCl2·8H2O, 4.6g Y(NO3)3·6H2O and 10kg deionized water and put them into a beaker and stir to dissolve them to obtain a mixed solution of metal ions.
[0119] (2) Weigh 650g NH4HCO3, 2.5g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0120] (3) Use a peristaltic pump to transfer the metal ion mixed solution and titrate it into the reaction vessel by spray titration. While titrating, vigorously stir the reaction solution. The spray titration speed is 150 ml / min and the stirring speed is 100 r / min.
[0121] (4) After titration, add 2000g of anhydrous ethanol to the solution and continue stirring for 20 min. Adjust the pH of the solution to 8 with ammonia water and then age it.
[0122] (5) After aging, discard the supernatant and pour the precipitate into a positive pressure filter for solid-liquid separation. After separation, add deionized water to the solid product for washing, stir for 30 minutes, and then pour it into the filter for solid-liquid separation again. The mass of deionized water is twice the mass of the solid product, and the washing is performed 3 times. After washing, add an equal mass of deionized water to the solid product and stir to form a suspension to obtain the precursor slurry.
[0123] (6) The precursor slurry was transferred using a peristaltic pump and dried and granulated using spray granulation to obtain precursor particles. The spray granulation temperature was 220 °C. The precursor particles were then sintered in a muffle furnace to obtain ZTA powder. The sintering temperature was 1100 °C and the holding time was 2 h. Steps (1) to (6) were repeated 10 times to prepare sufficient ZTA powder for subsequent use.
[0124] (7) Weigh 850g ZTA powder, 45g paraffin wax, 7.5g stearic acid, 30g acrylic resin, 37.5g polystyrene and 30g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0125] (8) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0126] (9) Place the injection feed particles in the hopper and use an injection molding machine to perform injection molding to obtain a ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 9 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 30 s.
[0127] (10) The ceramic chopping blanks were placed in a muffle furnace for pre-sintering. The sintering regime was to raise the temperature to 600℃ at 0.3℃ / min and hold for 0.5h, then raise the temperature to 1250℃ at 4℃ / min without holding, and finally raise the temperature to 1450℃ at 2℃ / min and hold for 3h.
[0128] (11) The pre-sintered ceramic blank is placed in a hot isostatic pressing sintering process at a temperature of 1450℃ for 1 hour. The sintered chopping knife is then ground, processed, and polished to obtain the ZTA ceramic chopping knife.
[0129] Comparative Example 6 A method for preparing a zirconia-toughened alumina ceramic chopping knife is basically the same as that in Example 1, except that step (3) does not use spray titration, but only ordinary titration. The specific steps are as follows: (1) Weigh 725.3g AlNH4(SO4)2·12H2O, 62.4g ZrOCl2·8H2O, 4.6g Y(NO3)3·6H2O and 10kg deionized water and put them into a beaker and stir to dissolve them to obtain a mixed solution of metal ions.
[0130] (2) Weigh 650g NH4HCO3, 2.5g polyethylene glycol 2000 and 10kg deionized water and place them in a reaction vessel and stir to dissolve them to obtain a precipitant solution.
[0131] (3) Use a peristaltic pump to transfer and titrate the metal ion mixture into the reaction vessel while vigorously stirring the reaction solution during titration. The titration speed is 150 ml / min and the stirring speed is 100 r / min.
[0132] (4) After titration, add 2000g of anhydrous ethanol to the solution and continue stirring for 20 min. Adjust the pH of the solution to 8 with ammonia water and then age it.
[0133] (5) After aging, discard the supernatant and pour the precipitate into a positive pressure filter for solid-liquid separation. After separation, add deionized water to the solid product for washing, stir for 30 minutes, and then pour it into the filter for solid-liquid separation again. The mass of deionized water is twice the mass of the solid product, and the washing is performed 3 times. After washing, add an equal mass of deionized water to the solid product and stir to form a suspension to obtain the precursor slurry.
[0134] (6) The precursor slurry was transferred using a peristaltic pump and dried and granulated using spray granulation to obtain precursor particles. The spray granulation temperature was 220 °C. The precursor particles were then sintered in a muffle furnace to obtain ZTA powder. The sintering temperature was 1100 °C and the holding time was 2 h. Steps (1) to (6) were repeated 10 times to prepare sufficient ZTA powder for subsequent use.
[0135] (7) Weigh 850g ZTA powder, 45g paraffin wax, 7.5g stearic acid, 30g acrylic resin, 37.5g polystyrene and 30g ethylene-vinyl acetate copolymer and mix them in a mixer to obtain injection feed. The temperature of the mixer is 165 ℃.
[0136] (8) Use a jaw crusher to crush the cooled feed to obtain injection feed particles with a size of 2mm to 5mm.
[0137] (9) Place the injection feed particles in the hopper and use an injection molding machine to perform injection molding to obtain a ceramic chopping green body. The injection temperature is 180℃, the injection pressure is 9 MPa, the molding holding pressure is 6 MPa, and the molding holding time is 30 s.
[0138] (10) The ceramic cleaver blanks were placed in a muffle furnace for pre-sintering. The sintering regime was to raise the temperature to 600℃ at 0.3℃ / min and hold for 0.5h, then raise the temperature to 1250℃ at 4℃ / min and hold for 3h, and finally raise the temperature to 1450℃ at 2℃ / min and hold for 3h.
[0139] (11) The pre-sintered ceramic blank is placed in a hot isostatic pressing sintering process at a temperature of 1450℃ for 1 hour. The sintered chopping knife is then ground, processed, and polished to obtain the ZTA ceramic chopping knife.
[0140] The morphology of the ZTA powder and the ZTA ceramic wedge obtained in Example 1 of the present invention, and the morphology of the ZTA powder obtained in Examples 1 and 2 were characterized: Figure 1 The morphology of the ZTA powder prepared in Example 1 shows that it is an agglomerate of less than 10 μm composed of nano-sized primary grains, indicating that the preparation of "controllable agglomeration powder" has been successfully achieved. Figure 2 The image shows the cross-sectional microstructure of the ZTA ceramic wedge prepared in Example 1, where the white portion represents zirconium oxide and the black portion represents alumina. The results show that the alumina grain size is approximately 1 μm, while the zirconium oxide grains are nanoscale. Both are uniformly distributed, and there are no obvious pores within the material. Figure 3 The ZTA powder prepared for Comparative Example 1 has a morphology that shows primary crystals that are plate-like and severely agglomerated because no ethanol was added. Figure 4For the ZTA powder prepared in Comparative Example 2, the dispersibility was significantly improved by adding anhydrous ethanol, a polar organic solvent, before titration, resulting in ZTA powder with fine primary grains and less agglomeration. However, if the dispersibility is too good and the powder is too fine, it will lead to difficulty in controlling subsequent processes, such as requiring more binder, low solid content, large sintering deformation, and deterioration of performance.
[0141] The performance of the ceramic chopping knives prepared in Examples 1-4 and Comparative Examples 1-6 of this invention was tested, and the results are shown in Table 1: Table 1. Performance comparison of ceramic chopping knives prepared in various embodiments and comparative examples
[0142] As shown in Table 1, Examples 1-4 all exhibited flexural strengths exceeding 650 MPa and Vickers hardness exceeding 21 GPa. In contrast, Comparative Example 1, due to its lamellar primary grains, was difficult to sinter densely, resulting in a relative density of only 87.3%. Comparative Example 3, due to its low ZTA powder calcination temperature, had incomplete grain development and low "agglomerate" strength, making it difficult to formulate high-solids-content feedstocks and achieve complete densification, resulting in poor mechanical properties. Comparative Example 4, due to its excessively high calcination temperature, experienced excessively large primary grains and high agglomerate strength, leading to decreased powder sintering activity. Neither of these examples achieved complete densification, thus reducing all properties. Although Comparative Example 2 prepared ZTA powder with fine and uniform primary grains, its high specific surface area also made it difficult to formulate high-solids-content feedstocks, resulting in large sintering shrinkage and easy defects during the binder removal process. Its strength and hardness were still lower than those of Example 1. Comparative Example 5, due to the absence of a low-temperature holding stage during sintering, resulted in incomplete solid solution of yttrium oxide and zirconium oxide, leading to the formation of impurity phases. Simultaneously, the toughening effect of zirconium oxide was weakened, resulting in lower performance. Comparative Example 6, using a conventional titration method (without spray titration) to prepare ZTA powder, exhibited poor dispersion uniformity of zirconium oxide and alumina, also contributing to performance degradation. In summary, this invention provides a method for preparing zirconium oxide-toughened alumina ceramic chopping tools. This method effectively increases the solid content of the injection feedstock while ensuring the ZTA ceramic chopping tools possess fine grains, high density, and excellent mechanical properties. This reduces sintering shrinkage and deformation, decreases subsequent processing, and ultimately achieves a balance between high yield and low cost.
[0143] While the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the invention. Any person skilled in the art can make many possible variations and modifications to the technical solutions of the present invention, or modify them into equivalent embodiments, without departing from the spirit and technical essence of the invention. Therefore, any simple modifications, equivalent substitutions, equivalent changes, and modifications made to the above embodiments based on the technical essence of the present invention, without departing from the content of the present invention, shall still fall within the scope of protection of the present invention.
Claims
1. A method for preparing a zirconia-toughened alumina ceramic cleaver, characterized in that, Includes the following steps: (1) Dissolve aluminum salt, zirconium salt and yttrium salt together in water to prepare a mixed solution of metal ions; (2) Mix the precipitant, dispersant and water to obtain a precipitant solution; (3) The mixed metal ion solution is spray-titrated into the precipitant solution while the reaction solution is stirred during titration; (4) After titration, a polar organic solvent is added to the reaction solution, stirring is continued, and the pH is adjusted to alkaline with ammonia water for aging; the polar organic solvent is miscible with water, has a surface tension lower than that of water, and a dielectric constant lower than that of water; the amount of the polar organic solvent used is 10% to 30% of the sum of the water mass in steps (1) and (2); (5) Separate the solid and liquid components of the aged product, wash it with water, and prepare a suspension as a precursor slurry; (6) The precursor slurry is granulated and calcined at 900℃~1100℃ to obtain ceramic powder; (7) The ceramic powder is mixed with a low molecular weight polymer, stearic acid, a medium molecular weight polymer, and a high molecular weight polymer to obtain an injection feed; the molecular weights of the low molecular weight polymer, the medium molecular weight polymer, and the high molecular weight polymer increase sequentially, and their thermal decomposition peak temperatures increase sequentially; the low molecular weight polymer is a flow agent; the medium molecular weight polymer and the high molecular weight polymer are both binders; the mass fraction ratio of the ceramic powder to the low molecular weight polymer, stearic acid, the medium molecular weight polymer, and the high molecular weight polymer is 75%–85%∶2%–10%∶0.5%–3%∶2%–10%∶4%–20%; (8) Cool and crush the injection feed to obtain injection feed particles; (9) The injection-feed particles are injection molded to obtain a ceramic chopping green body; (10) The ceramic green body is pre-sintered to obtain a ceramic body. The pre-sintering is a gradient heating sintering, including the first stage of heating to 500℃~700℃ and holding for 0.5 h~2 h, the second stage of heating to 1100℃~1300℃ and holding for 2 h~5 h, and the third stage of heating to 1350℃~1500℃ and holding for 2 h~5 h. (11) The ceramic blank is subjected to hot isostatic pressing sintering, grinding, processing and polishing to obtain a ceramic chopping knife; In step (4), the polar organic solvent is at least one of anhydrous ethanol, methanol, acetone and isopropanol; In step (7), the low molecular weight polymer is at least one of paraffin wax and beeswax; the medium molecular weight polymer is at least one of acrylic resin and polyethylene wax; and the high molecular weight polymer is at least one of polystyrene, ethylene-vinyl acetate copolymer, polyethylene, polypropylene and polyvinyl butyral.
2. The method for preparing the zirconia-toughened alumina ceramic cleaver according to claim 1, characterized in that, In step (1), the mass fraction ratio of the aluminum salt, zirconium salt, yttrium salt, and water is 5%–10% : 0.5%–1% : 0.01%–0.1% : 89%–94%; In step (2), the mass fraction ratio of the precipitant, dispersant and water is 4% to 14%: 0.01% to 1%: 85% to 95%.
3. The method for preparing the zirconia-toughened alumina ceramic cleaver according to claim 1, characterized in that, In step (1), the aluminum salt is ammonium aluminum sulfate, the zircon salt is zirconium oxychloride, and the yttrium salt is yttrium nitrate; In step (2), the precipitant is selected from at least one of ammonium bicarbonate and ammonium carbonate; the dispersant is selected from at least one of polyethylene glycol and polyvinylpyrrolidone.
4. The method for preparing the zirconia-toughened alumina ceramic cleaver according to claim 1, characterized in that, In step (3), the spraying rate is 20 ml / min to 250 ml / min, and the stirring rate is 50 r / min to 150 r / min; In step (4), the pH of the reaction solution after adjustment with ammonia is 7.6 to 9.0, and the aging time is 1 h to 24 h; In step (6), the granulation is carried out by spray granulation, the temperature of the spray granulation is 150℃~300℃; the calcination time is 1h~5h; In step (7), the mixing is carried out using an internal mixer, and the temperature of the internal mixer is set to 140℃~170℃.
5. The method for preparing the zirconia-toughened alumina ceramic cleaver according to claim 1, characterized in that, In step (9), the injection temperature used in the injection molding is 160℃~190℃, the injection pressure is 5MPa~15MPa, the molding holding pressure is 5MPa~10MPa, and the molding holding time is 20s~60s.
6. The method for preparing the zirconia-toughened alumina ceramic cleaver according to claim 1, characterized in that, In step (10), the heating rate of the first stage is 0.2℃ / min to 0.5℃ / min, the heating rate of the second stage is 2℃ / min to 5℃ / min, and the heating rate of the third stage is 2℃ / min to 5℃ / min.
7. The method for preparing the zirconia-toughened alumina ceramic cleaver according to any one of claims 1 to 6, characterized in that, In step (11), the temperature of hot isostatic pressing sintering is 1400℃~1500℃, and the holding time is 1h~3h.
8. The method for preparing the zirconia-toughened alumina ceramic cleaver according to any one of claims 1 to 6, characterized in that, In step (5), the water washing involves filtering the precipitate to obtain a solid product, adding water at a mass of 2 to 5 times that of the solid product, stirring, and filtering; the number of water washing cycles is 2 to 5.
9. The method for preparing the zirconia-toughened alumina ceramic cleaver according to any one of claims 1 to 6, characterized in that, In step (8), the size of the injection feed particles is 2mm to 5mm.
Citation Information
Patent Citations
Preparation method of zirconium oxide toughened aluminum oxide powder and ceramic
CN112456979A
High-performance aluminum oxide ceramic chopper and preparation method thereof
CN116003109A